Classroom behavior management practices in kindergarten classrooms: An observation study. - Beazidou, Eleftheria; Botsoglou, Kafenia; Andreou, Eleni (Έρευνα στην Εκπαίδευση, 2013)
The main purpose of this paper is to demonstrate the types of management practices that teachers use when disturbing behaviors occur in their classrooms. Teachers and children were observed in 14 kindergartens during daily classroom activities. Data was collected through the use of observation checklists, documents, and teacher’s short interviews. The present study distinguishes the classroom management practices into two broad categories: positive non - punitive practices and negative punitive practices. The results showed that teachers combine most of the non - punitive practices such as, establishing and re-establishing rules, encouraging children to be responsible, promoting students to discuss a topic involving behavior, emotions or situations of concern, etc., with punitive practices such as verbal reprimand, intervention by yelling etc. Research has yielded important information that has practical implications for the improvement of classroom behavior management practices.